2019
DOI: 10.1002/ccd.28097
|View full text |Cite
|
Sign up to set email alerts
|

In vivo validation of Dosemap software use in interventional cardiology with dosimetrics indicators and peak skin dose evaluation

Abstract: Objectives The aim of this study was to determine the accuracy of DoseMap™ software as compared to gafchromic film in real clinical practices. Background The radiation exposure from cardiovascular procedures could expose patients to potential risk of cancer and/or skin injury. New tools like Dosemap software were developed to estimate the patient skin dose in the cardiac catheterization laboratory. However, little data are available to validate this estimation of patient radiation skin dose. Methods This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…Various studies have compared skin dose measurements with SDM software. Some studies included real clinical cases [11,[13][14][15][16] while others used physical phantoms [8,10,15,[17][18][19]. The dosimetric capabilities and accuracy of the SDM products could strongly differ depending on the irradiation settings and the interventional X-ray system tested.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have compared skin dose measurements with SDM software. Some studies included real clinical cases [11,[13][14][15][16] while others used physical phantoms [8,10,15,[17][18][19]. The dosimetric capabilities and accuracy of the SDM products could strongly differ depending on the irradiation settings and the interventional X-ray system tested.…”
Section: Introductionmentioning
confidence: 99%
“…However, using cumulative air kerma as a surrogate for PSD is limited because it is estimated without considering the height of the table, distribution of the radiation dose caused by tube angulation, attenuation by the table, and backscatter radiation [8,9,46]. Recently, skin dose mapping software have been studied vigorously and several studies have reported promising results [7,[10][11][12][13][14][15]47]. It has the advantage of providing PSD and dose map is automatically calculated considering distribution of the radiation dose without interfering with the clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…To predict and appropriately manage the potential skin injury, it is important to estimate the peak skin dose (PSD), defined as the highest absorbed dose to the patient's skin [4,5]. Easily applicable methods in the clinical practice are indirect methods such as cumulative air kerma measured at the interventional reference point (IRP, defined as 15 cm from the isocenter toward the X-ray tube) and skin dose mapping [6][7][8][9][10][11][12][13][14][15]. However, these indirect methods may have limitations when compared to the direct measurement of PSD because the estimated position of the patient does not always reflect the actual position and the evaluation of the backscatter radiation is limited [9][10][11][12]14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main consequence of ionising radiation interactions with the radiochromic films is the film color alteration, whereas the alteration intensity is proportionate to the dose value. The quantitative post-irradiation analysis and determination of skin dose is strongly dependent on various film properties and performance under clinical irradiation conditions (Greffier et al, 2017;Didier et al, 2019). Major factors contributing to the variation in the film response are the energy dependence and dose rate dependence.…”
Section: Introductionmentioning
confidence: 99%